Assessing isometric hip strength in young professional soccer players: Does hip-flexion angle matter? - Taylor, J.; Pallotta, H.; Hunter, M.; Wright, M. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Hip and groin injuries are commonplace in soccer and often result in considerable time-loss [1]. The hip adductors contribute to sprint, jump, and change of direction [2], and deficits in isometric hip adductor strength are associated with groin injuries [3]. Similarly, hip abductor strength is associated with stability and landing mechanics [4], and strength deficits may be a risk factor for lower limb injuries [5]. This underlines the value of assessing isometric hip strength. Short and long-lever hip strength has been reported at various hip flexion angles [6-8], yet comparison between angles is lacking. This study assessed the effects of hip flexion angle on peak force production and relationship between angles in soccer players. METHODS: Twenty-four soccer players (Age 17.4 ± 0.8 years) completed 3 testing sessions during which isometric hip strength (i.e., adduction and abduction) was assessed at 45-, 60-, and 90-degree angles, using a fixed frame-dynamometer (Vald ForceFrame). Players completed testing in a counterbalanced order across a 2-week period and were in a similar physiological state for each. Three 5-s maximal voluntary contractions were completed in each position with a 30-s rest between trials. Peak force achieved across the trials for each limb was retained for analysis. A robust repeated measures ANOVA was used to detect changes between positions, with significance set at P<0.05 and Pearson`s correlations used to quantify associations. RESULTS: Significant mean differences were observed in peak adduction force between all positions. Mean differences were -25.9 ±23.1N (±95% confidence limit) and -33.4±19.1N for the right and left limbs, respectively, between 45- and 60-degrees; 46.8±23.2N and 32.6±19.9N for the right and left limbs, respectively, between 45- and 90 degrees; and 72.7±22.9N and 66.1±19.9N for the right and left limbs, respectively, between 60- and 90-degrees. Significant mean differences were observed in peak abduction force between 45- and 90- degrees, and 60 and 90-degrees. Mean differences were 32.2±20.8N and 25.7±21.1N for the right and left limbs, respectively between 45- and 90-degrees; and 42.4±20.9N and 41.6±21.3N for the right and left limbs, between the 60- and 90-degrees. Very large correlations were observed between adductor force at 45- and 90- degrees and force at 60 degrees (r = 0.77 to 0.87) and similarly for abductor force (r = 0.77 to 0.79) CONCLUSION: Peak adduction force varies between short-lever test positions, while peak abduction force varies between a 90-degree and other hip flexion angles. However, very large associations between peak adduction and abduction force at different hip flexion angles existed.